Citizens' Assessment on Programs for Education of the Local Government Unit of Banga, Aklan - Jyanee Loi D. Yecla; Cecilia T. Reyes; Cecile O. Legaspi; Anna Mae C. Relingo (Universal Journal of Educational Research)
Citizen Satisfaction Index System (CSIS) was used to assess the delivery of support to education initiatives in the municipality of Banga, Aklan, Philippines. The samples were determined using multiple application of stratified random sampling approach. In accordance with the Philippine Statistical Authority's Data on Census Population and Housing for 2015, barangays having a bigger share of the population contributed more respondents to the 150 targeted participants. Following the inclusion criteria, the probability respondents were chosen using the Kish Grid. Pre-numbered questionnaires were distributed, with odd numbers targeting male responders and even numbers targeting females. The following criteria were used to evaluate the respondents' assessments: awareness, availment of the program/service, satisfaction, and need for action. Furthermore, interviews were conducted to better understand and investigate the respondents' thoughts, behavior, and perspectives. The reasons for their reaction were also obtained. The data was provided in percentage as well as frequency distributions. The study inferred that awareness on alternative learning system and/or special education program should be improved since it is the only program that attained low rating for awareness. Most of the residents were not able to avail education programs because they have no household member who attends school. Majority of the respondents who availed the services were satisfied. However, scholarship and other assistance programs to students may be enhanced to improve service delivery. It is highly recommended by the citizens to improve accessibility to scholarship programs and other forms of financial assistance to students.